URGENSI SIYAQ DALAM PENAFSIRAN AL-QUR’AN - Syukraini Ahmad (Institut Agama Islam Negeri Bengkulu, 2017)
Siyâq is a sequence and coherence of sentences or situations of speech that can indicate or clarify the speaker’s intent. Thus, Siyaq is divided into two, namely first, Siyaq Lughawi / Maqaliy, the linguistic indicators used to establish the meaning of the text. Secondly, Siyaq Ghairu Lughawiy, an indicator that is not based on language, but based on many indicators in order to establish the true intent. In connection with the verses of the Qur’an, some experts suggest three kinds of Siyaq, namely: First, relating to one sura. In this section, Siyaq makes a surah connected from the beginning of the chapter to the end. Second, it deals with fragments of speech in one sura. Thirdly, Siyaq verse. There are many indicators that can be used to define Siyaq, of which the most important, that is, the history of the shohih which reaches his beloved circle to the Messenger of Allah, or known friends in the field of the Qur’an, language that is used in the Qur’an, or reason and reality, and the atmosphere of “kebatinan” verse. So, Siyaq is considered very urgent because the scholars agree to make it as one of the important factors in determining meaning. Furthermore, the function of siyaq as an explanatory meaning is six that is to clarify the things that are still global, set one meaning among the various possible meanings, reinforce the obvious, limit the scope of the general sentence (takhsis al’am), limit the absolute sentence, and to diversify meanings.